Biomass Carbon Content in Schima-Castanopsis Forest of Midhills of Nepal: A Case Study from Jaisikuna Community Forest, Kaski - Tripathi, Sushma; Thapa, Chandra Bahadur; Sharma, Amrit (Himalayan Biodiversity, 2017)
Forests are considered as both the source and sinks of carbon. Different types of forests have different carbon stock. Nepal's midhills community forests have high potentiality to sequester carbon. This paper analyzes the biomass carbon stock in Schima-Castanopsis forest of Jaisikuna community forests of Kaski district, Nepal. Forest area was divided into two blocks and 18 sample plots (9 in each block) were laid randomly. Diameter at Breast Height (DBH) and height of trees (DBH≥5cm) were measured using the DBH tape and clinometer. Leaflitter, herbs, grasses and seedling were collected from 1*1m2 plot and fresh weight was taken. Biomass of tree was calculated and below ground biomass is assumed 15% of above ground tree biomass. For calculating carbon stock, biomass is multiplied by default value 0.47. The above ground tree biomass (AGTB) carbon of chilaune, katus and other species was found 19.56 t/ha, 18.66 t/ha and 3.59 t/ha respectively. The AGTB of chilaune dominated, katus dominated and whole forest was found 43.78 t/ha, 39.83 t/ha and 41.81 t/ ha respectively. LHG carbon was found 2.73 t/ha. Below ground biomass carbon at whole forest was found 6.27 t/ha respectively. Total biomass and carbon at forest was found 108.09 t/ha and 50.80 t/ ha respectively. Difference in biomass and carbon content at chilaune dominated block and katus dominated block was found insignificant. Carbon estimation at forest of different elevation, aspect and location are recommended for further research.